MENUJU FIKIH YANG ADAPTIF: MAQASID AL-SYARI‘AH SEBAGAI KERANGKA PENILAIAN KUPON BERHADIAH - Khoiruddin, Ridhwan; Uzmawi, Cahyo Nurul; Al-Faiq, Naufal Ilham; Ramadan, Rizky Eriya (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2026)
The practice of prize coupons as a promotional strategy in the modern economy raises Islamic legal issues related to elements of gambling (maisir) and the transfer of assets without a legitimate basis. This study aims to analyze three models of prize coupons Model A (free coupons), Model B (purchase coupons), and Model C (sold coupons) based on the maqaṣid al-syari‘ah approach. This study uses a literature study method by examining the Qur’an, hadith, classical fiqh literature, and contemporary studies on speculative transactions. The results show that Model A is in accordance with sharia principles because it does not contain elements of betting. Model B is conditionally permissible, with validity dependent on price transparency and separation of contracts. Meanwhile, Model C is categorized as maisir because it contains speculation and the transfer of assets in a void manner. This study confirms that maqaṣid al-syari‘ah is a relevant evaluative framework for assessing contemporary promotional practices fairly and adaptively.